Diseño de un Modelo de Gestión de Mantenimiento para el Beneficio de Café del Río Tarrazú, propiedad de Cafetalera Tierras Ticas S. A. - Fernández-Granda, Ana Gabriela (Instituto Tecnológico de Costa Rica, 2017)
The present project had started operations in the Beneficio del Río Tarrazú, belongs to the Cafetalera Tierras Ticas S.A. It is located in Monterrey de Aserrí the main economic activity focus on the agroindustrial activity of the traditional coffee product through wet processing, since 1978. The project proposes the elaboration of a Maintenance Management Model that provides the necessary tools and methodologies according to the existing maintenance needs, since before starting the development of the project it is observed that no maintenance records are made, no record failures or causes in writing. As an initial part of the management model, an evaluation of the maintenance is carried out through the COVENIN 2500-93 standard, with the purpose of knowing the maturity of the organization in the maintenance, with the results of this evaluation the opportunities for improvement are identified. Next, the equipment is encoded, then a criticality analysis is carried out, which allows to classify the state in which the equipment is located and to select the critical ones to propose preventive maintenance activities. The documentation for maintenance control activities is designed, with the respective flow diagrams for its use, which allows carrying out a history and maintenance control. Maintenance indicators were defined by using the Balanced Scorecard methodology. The main indicators obtained are: the performance of continued improvement. In addition, a change strategy was proposed to implement the proposed action.
Proyecto de Graduación (Licenciatura en Mantenimiento Industrial) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electromecánica, 2017.
Keywords: Gestión de Mantenimiento; Análisis; Mantenimiento Preventivo; Trabajo; Indicadores; Research Subject Categories::TECHNOLOGY::Engineering mechanics